The division of castes among nations based on the work of M.R. Kukrit Pramoj - Thi Hang, Truong (RMUTSB ACADEMIC JOURNAL (HUMANITIES AND SOCIAL SCIENCES), 2025)
This article aims to investigate the division of castes among nations based on the work of M.R. Kukrit Pramoj and relies on the word "caste" as the grouping criteria. The results of the study therefore reflect the diversity of each society and between nations, rather than the division of the society into high-low levels that would cause social conflict. They also reveal differences in aspects of politics and administration, ways of life, including arts and culture. In terms of politics and administration, the British and French colonial cities distinguished the two great powers from Portugal and resulted in the natives having closer ties to Portugal than other Western nations. While Malaysia's elected "head of state" position for 5 years set the sultanate of Malaysia apart from the monarchs in general. In terms of lifestyle, 5 buttons on the Ratchapataen shirt distinguished Thais from Khmer, and the way of life of westerners who come to forestry in Lampang province set this group of Westerners apart from the natives. In terms of art and culture, Khon Luang and drama in Thailand are not only known as the most sublime, but it is also a divide between the people of Thailand and the Tributary states like Cambodia and Laos. Also, bathing while wearing clothes caused Thais, especially the central Thais in the pre-modern era, different from some peoples in Southeast Asia, such as people in Indonesia.